2013
DOI: 10.1016/j.ejps.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical classification of poorly soluble drugs with respect to “enabling formulations”

Abstract: The large number of drug candidates with poor dissolution characteristics seen in the past decade, has fostered interest in so-called "enabling formulations", i.e., formulations which shall make such drugs bio-available. Development of enabling formulations is currently being guided by the following (simplified) hypothesis: If a poorly soluble drug (BCS class II drug) can be transferred into a solubilized state, one can achieve an absorption profile close to that of a soluble drug (BCS class I drug). Thus, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(88 citation statements)
references
References 84 publications
1
87
0
Order By: Relevance
“…However, results from meta-analysis revealed that the extent of enhancement of in vivo oral bioavailability was much lower than that of in vitro performance. This may be attributed to the fact that the in vivo system is much more complicated and prediction of oral bioavailability enhancement by enabling formulations may need to take into account the inter-relationship of commonly used parameters and/or additional factors (Buckley et al, 2013). Identification of key influence factors that could help optimizing the PL-based formulation is thus essential in order to increase the overall enhancement effect on bioavailability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, results from meta-analysis revealed that the extent of enhancement of in vivo oral bioavailability was much lower than that of in vitro performance. This may be attributed to the fact that the in vivo system is much more complicated and prediction of oral bioavailability enhancement by enabling formulations may need to take into account the inter-relationship of commonly used parameters and/or additional factors (Buckley et al, 2013). Identification of key influence factors that could help optimizing the PL-based formulation is thus essential in order to increase the overall enhancement effect on bioavailability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The absence of a positive systemic food effect demonstrates that estimating formulation performance based on simple dissolution experiments does not always capture the key intraluminal processes determining drug absorption from enabling strategies. In order to fully assess the performance of enabling formulations, the absorption-determining intraluminal processes should be identified and integrated into in vitro models (Buckley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution of poorly soluble APIs is often the rate-limiting factor for oral bioavailability (1,2). Solubilityenhancing formulation strategies include particle size reduction and the use of pH modifiers, salts, co-crystals, pro-drugs, cyclodextrins, lipids, surfactants, self-emulsifying drug delivery systems, mesoporous drug delivery carriers, and amorphous solid dispersions (3)(4)(5)(6). The use of amorphous solid dispersions is of great interest in that these high-energy systems tend to lead to orders of magnitude increases in apparent solubility (7,8).…”
Section: Introductionmentioning
confidence: 99%